Evaluasi pertumbuhan nilai perusahaan bank syariah Indonesia selama 2020–2024 menggunakan rasio PBV sebagai indikator market value - Ahmad, Reki; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the company value of Bank Syariah Indonesia (BSI) using the Price to Book Value (PBV) ratio in the pre- and post-merger periods in 2021. The method used is descriptive with secondary data from financial reports and stock market data from 2020–2024. The results show that BSI’s post-merger PBV is in the range of 2.8–2.95, reflecting stability and high investor confidence in the company’s prospects. Despite experiencing fluctuations due to the integration process and economic conditions, the PBV trend continues to demonstrate a positive market perception. Factors influencing PBV include financial performance such as ROE, ROA, and EPS, macroeconomic conditions, and successful risk management and post-merger integration. A high PBV also indicates potential overvaluation if not accompanied by consistent performance. Thus, PBV is an important indicator in assessing BSI’s company value and investment attractiveness in the capital market.